Advances in Photocatalysis: A Microreview of Visible Light Mediated Ruthenium and Iridium Catalyzed Organic Transformations - Teegardin, Kip; Day, Jon I; Chan, John; Weaver, Jimmie (Organic process research & development, 2016)
Photocatalytic organic transformations utilizing ruthenium and iridium complexes have garnered significant attention due to the access they provide to new synthetic spaces through new reaction mechanisms. A survey of the photophysical data and the diversity of transformations that may be accomplished utilizing commercially available photocatalysts is contained herein.